Treatment of Ginger Industrial Waste Using the Carbon Dioxide Supercritical Extraction (CDSE) Method - Riyanto, Riyanto; Naeli Khusnul Maria; Elfara Rahmadhika Suwarno (EKSAKTA: Journal of Sciences and Data Analysis, 2026)
Ginger industrial waste is available in abundance, unprocessed and harmful to the environment because of its smells. Researchers propose that ginger industrial waste be processed using water distillation and Carbon Dioxide Supercritical Extraction (CDSE) methods. The purpose of this study was to utilize ginger industrial waste, which is currently discarded. Ginger industrial waste was collected from the ginger beverage industry. Essential oil was extracted from the waste using two methods: water distillation and CDSE. Both essential oils were characterized to determine their chemical components and composition, as well as their physical and chemical properties in accordance with the Indonesian National Standard for ginger essential oil (SNI 1312:2021). The characteristics analyzed included specific gravity, refractive index, optical rotation, and chemical compound profile, as determinated using GC-MS. The yields of essential oil obtained from the water distillation and CDSE methods were 0.18% and 0.36%, respectively. The results of the specific gravity, refractive index, and optical rotation tests for the two methods did not differ significantly. The chromatogram profiles of the two methods also did not differ significantly. The study concluded that the CDSE method was superior to the water distillation method. The CDSE method is faster, requires no fuel, produces higher yields, and is environmentally friendly.